(untitled) (American Journal of Islam and Society, 1999)
The relations between Muslim peoples and the West, and between Muslim peoples and forms of modernity, have become increasingly pressing issues of scholarly and political concern over the past twenty-five years. In part, this is due to the growing power of Islamism in the lives and politics of many Muslim societies and, in part, to the fact that some fonns of Islamism can appear to be profoundly hostile to all that the West represents. The growing presence of Muslim peoples in Western societies and the many assumptions which that presence calls into question has also caused scholars and politicians to focus on these relations. Add to this the fact that some leading members of the Western policy establishment, most notably the US political scientist S. P. Huntington, have come to talk in the post-cold war era of a “clash of civilizations” in which the clash between Islam and the West is the most profound and the most dangerous for world p e . This book, which contains sixteen essays by Muslim and non-Muslim scholars, mainly from institutions in Europe and the Arab world, sets out to address key issues in the relations between Muslims, modernity, and the West. It is the outcome of a symposium held in Toledo, Spain, in April 1996, which was prompted by the Eleni Nakou Foundation for the promotion of cultural contact and understanding among European peoples, and held under the auspices of the Jose Ortega y Gasset Foundation. &ma Martin Muiioz, professor of Sociology of the Arab and Islamic World at the Autonoma University of Madrid was the intellectual “playmaker” of the occasion. Due to its Islamic past and the fundamental role it played in transmitting Islamic learning and culture for the development of Christian Europe, Spain was a goad choice of location for the aonference ...